THE EFFECT OF PEOPLE'S BUSINESS CREDIT ON THE PERFORMANCE OF MSMES WITH DIRECT CASH ASSISTANCE AS A MODERATION VARIABLE - Jacob, Jufri; Utami, Eva Yuniarti; Rosmawati, Wati; Juminawati, Sri; Sahri, Yulian (ITB AAS Indonesia Surakarta, 2024)
Abstract This research is quantitative research with an exploratory approach, an approach that uses a number of previous studies as the main reference in order to obtain elements of novelty and research gaps in the research being carried out. The data used in this research is primary data that researchers obtained through online distribution to rural communities who have MSMEs with a net income of under 5 million. The questionnaire that the researchers distributed contained several statements, namely strongly agree, agree, normal/so-so, disagree and strongly disagree. These data were analyzed using the smart PLS 4.0 analysis tool. The result in this research show that the the Community Business Credit variable can have a positive relationship and have a significant influence on MSME performance because the P-Values value is positive and is below the significance level of 0.05, namely 0.013. This is because People's Business Credit can make MSME capital stronger so that MSME stakeholders can innovate more, produce more varied products, and other things so that ultimately they can improve MSME performance. In contrast to the results of the first hypothesis, in the results of the second hypothesis, the third table of the Path Coefficient shows results that are inversely proportional if the Direct Cash Assistance variable cannot influence employee performance because the P-Values value is above the 0.05 significance level, namely 0.062. This is because the Direct Cash Assistance does not relate to business needs but rather personal needs and other things. Thus, the first hypothesis in this research can be accepted and the second hypothesis in this research cannot be accepted. Keywords: People's Business Credit, Performance Of Msmes, Direct Cash Assistance